2014
DOI: 10.1155/2014/971890
|View full text |Cite
|
Sign up to set email alerts
|

Olive Leaf Extract Attenuates Obesity in High‐Fat Diet‐Fed Mice by Modulating the Expression of Molecules Involved in Adipogenesis and Thermogenesis

Abstract: The present study aimed to investigate whether olive leaf extract (OLE) prevents high-fat diet (HFD)-induced obesity in mice and to explore the underlying mechanisms. Mice were randomly divided into groups that received a chow diet (CD), HFD, or 0.15% OLE-supplemented diet (OLD) for 8 weeks. OLD-fed mice showed significantly reduced body weight gain, visceral fat-pad weights, and plasma lipid levels as compared with HFD-fed mice. OLE significantly reversed the HFD-induced upregulation of WNT10b- and galanin-me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
62
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 44 publications
2
62
1
Order By: Relevance
“…Previous studies show that the expression levels of UCP1 were significantly downregulated in sWAT by chronic HFD feeding (Fromme and Klingenspor 2011; Shen, et al 2014). In contrast to sWAT, BAT UCP1 had been shown to be induced by HFD feeding (Fromme and Klingenspor 2011; Shen et al 2014).…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Previous studies show that the expression levels of UCP1 were significantly downregulated in sWAT by chronic HFD feeding (Fromme and Klingenspor 2011; Shen, et al 2014). In contrast to sWAT, BAT UCP1 had been shown to be induced by HFD feeding (Fromme and Klingenspor 2011; Shen et al 2014).…”
Section: Resultsmentioning
confidence: 90%
“…In contrast to sWAT, BAT UCP1 had been shown to be induced by HFD feeding (Fromme and Klingenspor 2011; Shen et al 2014). To further investigate the effect of HFD on UCP1 expression in BAT and sWAT, we performed time course study with HFD feeding for 1, 12, 20 and 32 weeks.…”
Section: Resultsmentioning
confidence: 99%
“…In vitro studies using human cell lines have suggested that OLE has anti-inflammatory [3] and anti-cancer effects [2]. In vivo animal studies suggest that OLE attenuates obesity from a high fat diet [4] and reduces impacts resulting from inflammatory cytokine production and insulin resistance [5]. These studies showed altered expression of genes in relevant pathways.…”
Section: Introductionmentioning
confidence: 99%
“…In adult animals, measurements in peripheral organs have yielded mixed results, with consumption of a fat-rich diet found to either stimulate or have no effect on the expression of PPAR γ and PPAR α (Kannisto et al, 2006, McIlroy et al, 2013, Penna-de-Carvalho et al, 2014, Shamsi et al, 2014, Shen et al, 2014). The only available evidence in the brain shows an increase in mRNA levels of PPAR γ in the hypothalamus of diet-induced obese mice, with no change in expression of PPAR α or PPAR β/δ (Diano et al, 2011).…”
Section: Discussionmentioning
confidence: 99%